Role of seed priming using natural biostimulants in reducing salt stress effects by reshaping physio-biochemical and antioxidant defense systems in glycine max seedlings - Rady, Mostafa M.; Elkelish, Amr; Nady, Nada M.; Kusvuran, Sebnem; Kusvuran, Alpaslan; Shaaban, Ahmed; Alhaithloul, Haifa A S; Ali, Mohamed A. M.; Abu-Elsaoud, Abdelghafar M.; François, Tapsoba; Sayed, Ali A. S. (Frontiers in Plant Science, 2025)
Abiotic stress significantly damages crops, reducing global yields by over 50%. Among these challenges, salt stress poses a critical constraint that severely affects the growth, productivity, and quality of soybeans in various regions worldwide. Therefore, greenhouse pot experiments were conducted in the experimental farm of Fayoum University from May 1 to 15, 2024. Seed priming approach was performed using lemon fruit juice diluted to 4% (DLFJ4%) and bee honey diluted to 6% (DBH6%) as natural biostimulants. These biostimulants contain a wealth of growth-inducing compounds, including free amino acids, soluble sugars, antioxidants, vitamins, and essential nutrients. The purpose of this approach was to evaluate the effectiveness of DLFJ4% or DBH6% in mitigating the adverse effects of salt stress on the physio-biochemical and antioxidant defense systems in Glycine max seedlings. Salt stress was induced by irrigation with saline water, which was prepared by adding NaCl salt to normal water until EC = 8.60 dS m–1. The results showed that salt stress significantly increased superoxide (O2> •–), hydrogen peroxide (H2O2), electrolyte leakage (EL), malondialdehyde, and ABA levels, which were linked to enhanced activity of antioxidant enzymes. Conversely, salt stress led to a substantial decrease in seed germination, seedling fresh and dry weights, and root activity. Furthermore, the photosynthetic and gas exchange parameters, leaf integrity traits, nutritional status, and hormonal levels of seedlings were all notably reduced. However, seed priming in DLFJ4% or DBH6% considerably alleviated the salinity-induced oxidative damage, leading to a notable decrease in O2•–, H2O2, malondialdehyde, EL, and ABA contents. These biostimulants further enhanced the activity of ROS-scavenging enzymes, including SOD, CAT, APX, and GR. This was accompanied by increased levels of soluble sugars, free proline, antioxidants, phytohormones, and essential macro- and micronutrients, as well as improved K+/Na+ and Ca2+/Na+ ratios. Both biostimulants nourished soybean seedlings and improved their morphological, physiological, and biochemical properties while also reducing salt stress toxicity. Overall, DBH6% proved to be more effective than DLFJ4%. These findings suggest that DBH6% is a potent natural biostimulant that enhances the salinity tolerance of salt-stressed soybean plants and improves sustainable agricultural practices.